Proximal segment positioning with high oblique sagittal split osteotomy: indications and limits of intraoperative mobile cone-beam computerized tomography - Seeberger, Robin; Thiele, Oliver C.; Mertens, Christian; Hoffmann, Jürgen; Engel, Michael (Oral surgery, oral medicine, oral pathology and oral radiology, 2013)
Objective - The purpose of this study was to evaluate the indications and limits for intraoperative proximal segment positioning control by mobile cone-beam computerized tomography (CBCT). - Study Design - For mandible osteotomy in orthognathic surgery, the high oblique sagittal split osteotomy (HSSO) is our standard procedure. In 22 patients, positioning control of the proximal segment was performed during and after surgery to check this alternative osteotomy technique. - Results - The mean intercondylar distance increased 0.31 mm in all patients. No significant change of the condyle positions was found in the axial and coronal planes. In the sagittal plane a significant change was found. In 1 case, revision was required because of a lateral shifting of the condyles. - Conclusions - Intraoperative positioning control with CBCT is an effective and reliable method to avoid condyle malpositions. Only minor position changes occur when using HSSO in orthognathic surgery, without compromising temporomandibular joint function postoperatively.